2012
DOI: 10.1186/1475-2875-11-168
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 (TLR9) polymorphism associated with symptomatic malaria: a cohort study

Abstract: BackgroundIn areas mesoendemic for malaria transmission, symptomatic individuals play a significant role as reservoirs for malaria infection. Understanding the pathogenesis of symptomatic malaria is important in devising tools for augmenting malaria control. In this study, the effect of TLR9 polymorphisms on susceptibility to symptomatic malaria was investigated among Ghanaian children.MethodsFour hundred and twenty nine (429) healthy Ghanaian children, aged three to eleven years (3–11 years), were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
5
30
2
2
Order By: Relevance
“…Consistent with our study, two separate studies, carried out in Brazil and Iran, have recently revealed no impact of individual TLR9 (Ϫ1237T/C) promoter polymorphism on susceptibility to mild malaria in their respective populations (30,65). Moreover, the TLR9 (Ϫ1237TT) genotype has only been associated with low parasitemia but not increased susceptibility to clinical malaria in Ghanaian children aged 3 to 11 years (40). Investigations with Gambian and Malawian children less than 5 years old characterized by mixed clinical phenotypes (cerebral and/or severe malaria anemia) did not show any association between the TLR9 (Ϫ1237T/C) polymorphisms and severe malaria (13).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with our study, two separate studies, carried out in Brazil and Iran, have recently revealed no impact of individual TLR9 (Ϫ1237T/C) promoter polymorphism on susceptibility to mild malaria in their respective populations (30,65). Moreover, the TLR9 (Ϫ1237TT) genotype has only been associated with low parasitemia but not increased susceptibility to clinical malaria in Ghanaian children aged 3 to 11 years (40). Investigations with Gambian and Malawian children less than 5 years old characterized by mixed clinical phenotypes (cerebral and/or severe malaria anemia) did not show any association between the TLR9 (Ϫ1237T/C) polymorphisms and severe malaria (13).…”
Section: Discussionsupporting
confidence: 77%
“…Since previous geneticsbased studies have thoroughly investigated SNPs (41,47) and haplotypes (40,46), we investigated the effect of cross-SNP combinations in conditioning SMA. We examined the associations between Fc␥RIIIA (Ϫ176F/V) and TLR9 (Ϫ1237T/C) promoter-variant combinations and susceptibility to SMA (Hb Ͻ 6.0 g/dl) in children (aged 3 to 36 months) residing in this area of western Kenya where P. falciparum transmission is holoendemic.…”
mentioning
confidence: 99%
“…Although some studies have reported no association between T-1486C and malaria susceptibility or severity 7,20,22,24,27,30 , we observed that the -1486C allele was a risk factor for severe malaria and high parasite load, which is in line with previous findings 21,24 . Moreover, -1486C has been associated with an increased risk of low birth weight in term infants born to P. falciparum-infected pregnant women 25 .Consistent with these findings, the meta-analysis of the T-1486C variant revealed a significant association with SM under the allele contrast (T vs. C) and homozygous (TT vs. CC) genetic models.…”
supporting
confidence: 82%
“…In addition, our recent observation of opposing associations of the -1237C allele with different sub-clinical severe malarial phenotypes such as single organ dysfunction (SOD) vs. multi-organ dysfunction (MODS) 2 suggests that phenotype misclassification in malaria could also lead to a reduction in the power to detect the contribution of this variant. This may explain the lack of observed associations between the T-1237C variant and susceptibility or resistance to malaria 22,27,29,30 , in addition to other factors. Therefore, future studies examining large sample sizes of malaria-infected patients categorized into required phenotype classes from different ethnic populations and belonging to different age groups are eagerly awaited for confirmation.…”
mentioning
confidence: 79%
“…Patients with chronic HBV infection were enrolled in this study (n = 1191, female, 424; male, 767; median age, 36; range, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], and the control population demonstrated previous HBV clearance (n = 273; female, 111; male, 162; median age, 42; range, 33-49). A significant difference was found between HBV clearance and chronic HBV infection for age (P < 0.0001).…”
Section: Patientsmentioning
confidence: 99%